The relationship between objectively measured physical activity and parameters of disease control in an African population of type 2 diabetes mallitus - Siddiqui, Muhammad Abid (My University, 2018)
BACKGROUND: The incidence of type 2 Diabetes Mellitus (T2DM) is increasing rapidly. This is possibly due to increasing obesity, reduced level of activity, sedentary lifestyle, aging population and industrialization. AIM: The primary objective of this study is to ascertain the level of activity using a pedometer in patients with T2DM. The secondary objectives are: (1) to correlate the baseline level of activity with body mass index (BMI), HbA1c and blood pressure (BP), (2) to assess whether 7000 steps a day influence HbA1c and BP over a 3-month period. METHOD: We screened 110 patients; 95 patients (n=95) completed the study. At the first visit HbA1c, BMI and BP were measured. At the end of the first month baseline physical activity (PA) was recorded using pedometers. Patients were divided into two groups: active (n=50) and control (n=45). Patients in the active group were asked to walk a minimum of 7000 steps/day. The control group were asked to continue their usual activity. These patients were followed up monthly over a period of 3 months. At each visit BMI, BP and step counts were recorded. HbA1c was measured only at the first and last visit. RESULT: Activity levels increased significantly in the active group throughout the study. Mean step count for the control group at baseline was 2923.1 ±1136.9, which increased to 3431.2 ±1251.7 by the end of the study. Mean step count for the active group at baseline was 4609.9±1702.1, which increased to 7244.8±1419.4 by the end of the study. The difference between control and active group was statistically significant (p < 0.001). Systolic and diastolic BP decreased significantly in both groups (p= 0.017) for systolic BP and (p= 0.002) for diastolic BP but no interaction found between the groups as systolic and diastolic BP decreased at the same rate over time in both groups. HbA1c decreased by 1.04% in active group, this difference was statistically highly significant (p <0.001) CONCLUSION: Increase in activity levels decreases HbA1c by 1.04 percentage point over 3 months in T2DM (p<0.001), which is statistically significant.
A research report submitted to the Faculty of Health Science, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Medicine in the branch of Internal Medicine. Johannesburg 2018